2006
DOI: 10.1576/toag.8.4.251.27276
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of tubal ectopic pregnancy: availability of training

Abstract: Key content:• A recent RCOG guideline stated that, in a woman who is haemodynamically stable, a laparoscopic approach to the surgical management of tubal ectopic pregnancy is preferable to an open approach.• Two national surveys showed that the technique was employed routinely in only 27% and 35% of cases.• In surveys, trainees in obstetrics and gynaecology frequently commented that they needed more supervision by consultants when carrying out this procedure. Learning objectives:• To learn about why improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…This has also been identified in a survey amongst Welsh trainees [10] and, hence, probably reflects the status of training programmes all over the UK. As a matter of urgency, hospitals must be encouraged to provide accommodation and equipment for simulator training.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…This has also been identified in a survey amongst Welsh trainees [10] and, hence, probably reflects the status of training programmes all over the UK. As a matter of urgency, hospitals must be encouraged to provide accommodation and equipment for simulator training.…”
Section: Resultsmentioning
confidence: 53%
“…The literature suggests that laparoscopy is better and more cost-effective than laparotomy in the surgical management of ectopic pregnancy [5], and the RCOG recommends its use in its guideline on ectopic pregnancy [9]. In a recent Welsh survey, 30% of the respondents stated that ectopic pregnancy was managed laparoscopically only during routine hours in some trusts [10]. Such out-of-hours management of ectopic pregnancy further limits training and suggests that some consultants are either not trained or are reluctant to come in from home when on-call to do the procedure laparoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1980s, a doctor would have spent 40,000 hours in training before appointment as a Consultant and now the figure is just over 12,000 (Qureshi et al 2006). Providing training to produce Consultants of similar quality as in the past in a shorter period is challenging and requires using every single teaching and training opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…RCOG is currently examining the role of simulators in formal training. A regional study from the UK revealed that all hospitals had the necessary laparoscopic equipment; so, simulator training could be a meaningful adjunct in augmenting training across the board [24]. The potential value of a simulator in such training is further emphasised by the anecdotal evidence that increasing medical or conservative management of patients with ectopic pregnancy reduces the opportunity for surgical training in theatre.…”
Section: Discussionmentioning
confidence: 99%